2021
DOI: 10.3390/ijms22083937
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Methylation Mapping Using Nanopore Sequencing Technology Identifies Novel Tumor Suppressor Genes in Hepatocellular Carcinoma

Abstract: Downregulation of multiple tumor suppressor genes (TSGs) plays an important role in cancer formation. Recent evidence has accumulated that cancer progression involves genome-wide alteration of epigenetic modifications, which may cause downregulation of the tumor suppressor gene. Using hepatocellular carcinoma (HCC) as a system, we mapped 5-methylcytosine signal at a genome-wide scale using nanopore sequencing technology to identify novel TSGs. Integration of methylation data with gene transcription profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…As shown by the Kaplan-Meier plot ( p -value<0.05), 11 genes were significantly associated with overall survival of patients ( Supplementary File S1 ). Downregulation of tumor suppressor genes function importantly in cancer formation and progression, which involves alteration of epigenetic modifications in genome-wide ( Davenport et al, 2021 ). Combined with transcriptome, six genes could be regarded as tumor suppressor genes ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown by the Kaplan-Meier plot ( p -value<0.05), 11 genes were significantly associated with overall survival of patients ( Supplementary File S1 ). Downregulation of tumor suppressor genes function importantly in cancer formation and progression, which involves alteration of epigenetic modifications in genome-wide ( Davenport et al, 2021 ). Combined with transcriptome, six genes could be regarded as tumor suppressor genes ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent data identified 161 putative driver genes that are associated with 11 recurrently altered pathways in HCC development [ 4 ], and these mutations were not observed in chronic hepatitis or cirrhosis (preneoplastic stages). Interestingly, 28% of the altered gene products play a role in chromatin remodeling, suggesting that abnormal chromatin remodeling results in a cancer-specific expression of a subset of genes [ 7 , 8 , 26 ]. Indeed, DNase-seq data which map the chromatin accessibility revealed that chromatin at the putative promotor region of seven out of nine HCC-specific lincRNAs is opened in HCC but not in normal liver ( Figure 1 B).…”
Section: Discussionmentioning
confidence: 99%
“…It shows the need for single-cell epigenetic technology capacity to truck drug-induced tumor evolution for the timely intercession of the treatment [ 293 ]. In hepatocellular carcinoma, identification of the modification status of tumor suppressor genes using nanopore sequencing showed around 10 potential tumor suppressor gene candidates and the glucokinase gene, more validated to involve in HCC development [ 375 ]. Nanopore sequencing allows whole-genome sequencing with the possible identification of epigenetic modifications in lung cancer cell line LC2/ad gene [ 376 ].…”
Section: Nanopore Sequencing For Epigenetic Tumor Heterogeneitymentioning
confidence: 99%